Perbandingan Kecepatan Pencarian Antara Binary Search Tree dan Array - Tirta, Zidan Firdaus (Maliki Interdisciplinary Journal, 2023)
This study compares the search speed between Binary Search Tree (BST) and Array in various scenarios. Through a series of experiments using the Java programming language, we analyze their performance in ordered, random, and reverse data situations. The results show that in the case of sorted data, Array has an advantage in searching. However, on random data, BST provides faster and more stable search results. For reversed data, Array is also superior in terms of search speed. The resulting recommendation is to use BST for searching in complex random data, while Array is more suitable for sorted or reversed data. Understanding these comparisons can help developers choose data structures that match application needs and optimize search performance.